Ethanol production from rice hull using Pichia stipitis and optimization of acid pretreatment and detoxification processes. (27th April 2016) - Germec, Mustafa; Kartal, Fatma Kubra; Bilgic, Merve; Ilgin, Merve; Ilhan, Eda; Güldali, Hazal; Isci, Aslı; Turhan, Irfan
Abstract : The goal of this study was to produce ethanol from rice hull hydrolysates (RHHs) using Pichia stipitis strains and to optimize dilute acid hydrolysis and detoxification processes by response surface methodology (RSM). The optimized conditions were found as 127.14°C, solid:liquid ratio of 1:10.44 (w/v), acid ratio of 2.52% (w/v), and hydrolysis time of 22.01 min. At these conditions, the fermentable sugar concentration was 21.87 g/L. Additionally, the nondetoxified RHH at optimized conditions contained 865.2 mg/L phenolics, 24.06 g/L fermentable sugar, no hydroxymethylfurfural (HMF), 1.62 g/L acetate, 0.36 g/L lactate, 1.89 g/L glucose, and 13.49 g/L fructose + xylose. Furthermore, RHH was detoxified with various methods and the best procedures were found to be neutralization with CaO or charcoal treatment in terms of the reduction of inhibitory compounds as compared to nondetoxified RHH. After detoxification procedures, the content of hydrolysates consisted of 557.2 and 203.1 mg/L phenolics, 19.7 and 21.60 g/L fermentable sugar, no HMF, 0.98 and 1.39 g/L acetate, 0 and 0.04 g/L lactate, 1.13 and 1.03 g/L glucose, and 8.46 and 12.09 g/L fructose + xylose, respectively. Moreover, the base‐line mediums (control), and nondetoxified and detoxified hydrolysates were used to produce ethanol by using P. stipitis strains. The highest yields except that of base‐line mediums were achieved using neutralization (35.69 and 38.33% by P. stipitis ATCC 58784 and ATCC 58785, respectively) and charcoal (37.55% by P. stipitis ATCC 58785) detoxification methods. Results showed that the rice hull can be utilized as a good feedstock for ethanol production using P. stipitis. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:872–882, 2016